Energy Markets and EMEA Stocks: Asymmetric TVP-VAR Connectedness and Investment Strategies - Sharma , Sourav; Katoch , Rupinder; Peer , Ubaid Ahmad (International Journal of Accounting and Economics Studies, 2025)
This study examines the dynamic transmission of shocks between key energy markets and selected equity markets in the Europe, Middle East, and Africa (EMEA) region using an asymmetric time-varying parameter vector autoregression (TVP-VAR) framework. Our daily dataset includes Clean Energy, Natural Gas, Crude Oil, and Heating Oil and eleven EMEA stocks (Czech Republic, Hungary, Kuwait, Qatar, Saudi Arabia, Poland, UAE, Egypt, Greece, South Africa, and Turkey) spanning from May 1, 2015 to Dec 31, 2024. The analysis reveals a moderate Total Connectedness Index (TCI) under aggregate shocks, with spikes during major global disruptions such as oil and climate related crisis, the COVID-19 pandemic, Russia-Ukraine war, and the Iran Israel war. Positive shocks exhibit stronger spillovers, peaking at over 60% TCI, driven by synchronized recovery periods, while negative shocks show lower but significant connectedness. Clean Energy consistently emerges as a dominant net transmitter across all regimes, while Natural Gas and certain equity markets, such as the UAE and Greece, act as net receivers. Network visualizations highlight Qatar’s prominence in positive shock regimes and Clean Energy’s systemic role during downturns. These findings underscore the asymmetric nature of shock transmission, offering critical insights for portfolio diversification, hedging strategies, and systemic risk monitoring in a globally integrated financial environment.